2011
DOI: 10.1007/s10103-010-0868-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acid and laser etching on shear bond strength of conventional and resin-modified glass-ionomer cements to composite resin

Abstract: Success in sandwich technique procedures can be achieved through an acceptable bond between the materials. The aim of this study was to compare the effect of 35% phosphoric acid and Er,Cr:YSGG laser on shear bond strength of conventional glass-ionomer cement (GIC) and resin-modified glass-ionomer cement (RMGIC) to composite resin in sandwich technique. Sixty-six specimens were prepared from each type of glass-ionomer cements and divided into three treatment groups as follows: without pretreatment, acid etching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
2
20
1
8
Order By: Relevance
“…Some studies have demonstrated that acid etching enhances the bond strength due to increases in mechanical retention 8) ; however, this has not been confirmed by other studies 9,10) . Such controversial results have been reported based on the bond between GICs and resin composites.…”
Section: Introductionmentioning
confidence: 89%
“…Some studies have demonstrated that acid etching enhances the bond strength due to increases in mechanical retention 8) ; however, this has not been confirmed by other studies 9,10) . Such controversial results have been reported based on the bond between GICs and resin composites.…”
Section: Introductionmentioning
confidence: 89%
“…In fact, the ability of this laser system to remove tissues with higher water content (like carious dentin) faster than healthy tooth structure offers a unique minimally invasive, selective caries removal potential [22]. Lasers also demonstrate many other benefits, including a caries-preventive effect [23,24], reduced need for acid etching of the prepared tooth structure [25], improved bond strength in composite resin restorations and glass ionomer cements [26], and a comparable degree of micro-leakage with solvent-free bonding agents, as compared to conventional rotary instruments [27]. Additionally, cavity disinfection of up to 0.5 mm below the surface was observed using the Er,Cr:YSGG laser system [28].…”
Section: Discussionmentioning
confidence: 99%
“…In posterior teeth, pain was most prevalent in class 2, though not to a statistically significant level. A closer look at prevalence of pain, with respect to patient age, found that young adults, age [26][27][28][29][30][31][32][33][34][35], are the most likely to experience pain with laser preparations, when using the Er,Cr:YSGG system. This finding mimics the dental anxiety study by Stouthard et al [33], whereby the 26-35-year age group was the most likely to experience high levels of dental anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The bonding of resin composite material to the tooth structure prepared with different types of lasers has been reported (Visuri et al, 1996;Armengol et al, 1999;Martínez-Insua et al, 2000;Carrieri et al, 2007;Ekworapoj et al, 2007;Lee et al, 2007;de Carvalho et al, 2008;Gurgan et al, 2008;Chou et al, 2009). These studies reported variable results comparing the bond strengths of composite resin to a laser-prepared and acid etched dentin surface, and suggested that the laser preparation is more effective than etching in bonding strength of the composite resin to the tooth structure (Obeidi et al, 2010;Turkmen et al, 2010;Navimipour et al, 2011). This study compared the in vitro SBS of two different adhesive systems to dentin treated with an Er,Cr:YSGG laser.…”
Section: Discussionmentioning
confidence: 99%